LQG control-aware resource scheduling method for IEEE 802.11ax networks - Meng ZHENG; Lei ZHANG; Wei LIANG (Tongxin xuebao)
Due to the advantages in low cost, ease of maintenance and license-exempt spectrum, etc, IEEE 802.11ax is widely adopted in industrial control applications.For a wireless networked control system based on IEEE 802.11ax, a control-aware resource scheduling method was proposed to support the wireless high-speed control of multiple control systems.Firstly, considering the packet dropout problem of sensing data in IEEE 802.11ax, the optimal state estimator and the linear quadratic Gaussian (LQG) control of the studied control system were given.Secondly, the dependency between the LQG performance and the transmission reliability of IEEE 802.11ax was analyzed, the expected LQG performance minimization problem of resource scheduling was formulated, and further, an LQG control-aware resource scheduling (LCARS) method was proposed.Finally, the effectiveness of the LCARS method was demonstrated via extensive simulations.LCARS can be applied to smart factory applications including navigation of automated guided vehicles, remote control of robots and so on.